Stiffness of skinned rabbit psoas fibers in MgATP and MgPPi solution. - Brenner, B. (The Biophysical Society, 1986)
The stiffness of single skinned rabbit psoas fibers was measured during rapid length changes applied to one end of the fibers. Apparent fiber stiffness was taken as the initial slope when force was plotted vs. change in sarcomere length. In the presence of MgATP, apparent fiber stiffness increased with increasing speed of stretch. With the fastest possible stretches, the stiffness of relaxed fibers at an ionic strength of 20 mM reached more than 50% of the stiffness measured in rigor. However, it was not clear whether apparent fiber stiffness had reached a maximum, speed independent value. The same behavior was seen at several ionic strengths, with increasing ionic strength leading to a decrease in the apparent fiber stiffness measured at any speed of stretch. A speed dependence of apparent fiber stiffness was demonstrated even more clearly when stiffness was measured in the presence of 4 mM MgPPi. In this case, stiffness varied with speed of stretch over about four decades. This speed dependence of apparent fiber stiffness is likely due to cross-bridges detaching and reattaching during the stiffness measurement (Schoenberg, 1985. Biophys. J. 48:467). This means that obtaining an estimate of the maximum number of cross-bridges attached to actin in relaxed fibers at various ionic strengths is not straightforward. However, the data we have obtained are consistent with other estimates of cross-bridge affinity for actin in fibers (Brenner et al., 1986. Biophys. J. In press.) which suggest that ~60-90% of the cross-bridges attached in rigor are attached in relaxed fibers at an ionic strength of 20 mM and ~2-10% of this number of cross-bridges are attached in a relaxed fiber at an ionic strength of 170 mM.